Analisis Efektivitas Penggunaan Media Sosial Tiktok Sebagai Sarana Promosi Pada Galeri Pusat Oleh-Oleh UMKM Karawang - Aura Aulia; Dedi Mulyadi; Sungkono (CV. ITTC INDONESIA, 2024)
This study aims to analyze the effectiveness of using the Tiktok application as a means of promotion through social media. Galeri Pusat Oleh-Oleh UMKM Karawang must be able to keep up with the technological developments that occur. At present, the online promotion strategy at the Galeri Pusat Oleh-Oleh UMKM Karawang has not been able to attract maximum consumer interest. This research uses the post-positivism paradigm with qualitative methodology through library research or literature study. The analysis model used in this research is the Three Layers of Social Media Analysis. The results of this study indicate that the public's brand awareness Galeri Pusat Oleh-Oleh UMKM Karawang has increased, as evidenced by the number of followers of the Tiktok @galerioleholeh_krw account increasing from May 2024 to June 2024. However, the effectiveness of using Tiktok social media as a means of promoting Galeri Pusat Oleh-Oleh UMKM Karawang can be said to be ineffective. Galeri Pusat Oleh-Oleh UMKM Karawang has only reached the second level of brand awareness, namely brand recognition. The results of the analysis through the Three Layers Of Social Media Analysis can be said to be ineffective. In the third stage of this analysis model, the gallery has not implemented it.